Exploiting the Role of TolC in Pathogenicity: Identification of a Bacteriophage for Eradication of Salmonella Serovars from Poultry - Ricci, Vito (American Society for Microbiology (ASM), 2010)
Using a screening procedure, three bacteriophages, ST27, ST29, and ST35, were identified with selective activity for Salmonella enterica serovar Typhimurium (SL1344) but not SL1344 tolC::aph. Overproduction of TolC led to a lower efficiency of plating (EOP), further suggesting that TolC was the target receptor. Activity against other serovars of Salmonella was observed but not against other species of Enterobacteriaceae. This study provides proof of principle that bacteriophages can be active against the outer membrane protein of tripartite resistance-nodulation-division (RND) efflux pumps and so could be used to reduce the numbers of Salmonella cells in animals reared for food production.